Peran Akreditasi Dalam Menarik Minat Mahasiswa Memilih Perguruan Tinggi Swasta Bermutu Di Kota Pekanbaru - Prama Widayat (UHN IGB Sugriwa Denpasar, 2018)
The ability of the community to meet the needs of life is increasingly difficult, especially to meet the needs of higher education for their children, so that children who graduate from high school choose to work while studying. This causes campuses to seize this opportunity by providing employee classes or on weekends so that they can accommodate market needs, but still maintain quality standards, easy but not easy. About 45% of new students want night classes.